2021
DOI: 10.4269/ajtmh.20-0747
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Village Health Workers’ Ability to Perform and Interpret Rapid Diagnostic Tests for Malaria 4 Years after Initial Training: A Cross-Sectional Study

Abstract: Village health workers (VHWs) in Bugoye subcounty, Uganda, provide integrated community case management (iCCM) care to children younger than 5 years for malaria, pneumonia, and diarrhea. We assessed the longevity of VHWs' skills in performing and reading malaria rapid diagnostic tests (RDTs) 4 years after initial training, comparing VHWs who had completed initial iCCM training 1 year before the study with VHWs who had completed training 4 years before the study. Both groups received quarterly refresher trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…iCCM is a component of a larger VHW strategy, wherein VHWs treat childhood killer diseases within 24 h of symptom onset in order to save lives [ 2 ]. Trained community health workers (VHWs) treat paediatric malaria, pneumonia, and diarrhoea under the iCCM approach, typically in a community setting as opposed to a medical facility [ 2 , 8 ]. Consequently, iCCM lowers out-of-pocket costs, improves access to care, and brings treatment closer to home [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…iCCM is a component of a larger VHW strategy, wherein VHWs treat childhood killer diseases within 24 h of symptom onset in order to save lives [ 2 ]. Trained community health workers (VHWs) treat paediatric malaria, pneumonia, and diarrhoea under the iCCM approach, typically in a community setting as opposed to a medical facility [ 2 , 8 ]. Consequently, iCCM lowers out-of-pocket costs, improves access to care, and brings treatment closer to home [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a clinical algorithm, the VHWs diagnose and treat malaria, pneumonia, and diarrhoea. This involves giving any child who presents with a subjective fever a rapid diagnostic test (RDT) for malaria and interpreting the test's results [ 8 ]. By improving access to timely care, iCCM may be able to lower morbidity and death rates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…(12)(13)(14) Evaluations of such programs have demonstrated that CHW are able to provide a high quality of care for malaria by utilizing malaria rapid diagnostic tests (mRDTs) for diagnosis. (15)(16)(17) The quality of pneumonia management is less consistent. (15,18) According to the iCCM algorithm, children who have both cough and fast breathing (i.e., tachypnea) are diagnosed with pneumonia and treated with antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The results of many studies have shown that the use of mobile education helps in managing diseases such as AIDS, tuberculosis, diabetes and cerebral palsy [8][9][10][11]. In recent years, mobile technology has also been used to monitor malaria treatment [12][13]. The aims of this study were to design an educational software for malaria and evaluate the satisfaction level of the software application among students of Vector Biology and Disease Control in Kerman University of Medical Sciences.…”
Section: Introductionmentioning
confidence: 99%